Beyond the operating room: Comparing surgical outcomes of a public insurance programme in Khyber Pakhtunkhwa - Asma Altaf Hussain Merchant; Shifa Salman Habib; Kiran Sohail Azeemi; Waqas Hameed; Junaid Ur Rehman Siddiqui; Sameen Siddiqi; Adil Haider (Journal of the Pakistan Medical Association, 2024)
Objective: To estimate the utilization of public insurance for surgical interventions in Khyber Pakhtunkhwa, Pakistan, andcompare surgical outcomes between insured and uninsured patients. Methods: We retrospectively extracted data from one public and three private tertiary hospitals of Khyber Pakhtunkhwa(KP) that are empanelled under the Sehat Card Plus (SCP) Programme. Secondary Data was collected for a period of 16months, from 1st June 2021 to 30th September 2022 both electronically and manually. The data collection process tookplace from October 2022 to December 2022. Patients undergoing exploratory laparotomy, lower (uterine) segmentcaesarean section (LSCS), or open reduction internal fixation (ORIF) of fractures were included. Extracted data includeddemographic details, payment status (SCP user/non-user), and surgical outcomes [in-hospital mortality, length of stay (LOS),14- and 30-day readmission]. Multivariable regression models were created to determine the association of SCP use withsurgical outcomes. Results: Records of 1,853 patients were analysed. The mean age was 28.74±12.75 years. A total of 582 (31.41%) patientsutilized SCP for their treatment,429 (73.71%) of whom underwent LSCS. Overall mortality rate was 17 (0.92%). Comparedwith SCP non-users, SCP users had a significantly higher LOS (standardised beta: 0.52, 95% CI: 0.08-0.97) and lower 14-dayreadmission rate (OR: 0.64, 95% CI: 0.41-1.00). However, no significant difference was observed for 30-day readmission. Conclusion: Significantly prolonged LOS in SCP users can lead to over-utilisation of available assets. However, a lower 14-day readmission rate was also noted among the SCP users. To ensure optimal outcomes among patients and adequate useof resources, continuous monitoring and changes are required for such public insurance programmes in low-resourcesettings. Keywords: Health insurance, National health programs, Universal health insurance, Treatment outcome